PERILAKU CARING PERAWAT DENGAN TINGKAT KEPUASAN PASIEN di RSUD H. ANDI SULTHAN DAENG RADJA KAB. BULUKUMBA - Haerani; Haerati (Jurnal Kesehatan Panrita Husada, 2017)
The phenomenon that is happening now is that many nurses pay little attention to safety and comfort and are not concerned with patient complaints so that patients are less satisfied in the nursing services provided. This study aims to determine the relationship of nurses caring behavior with the level of patient satisfaction in the Seruni care room at H. A. Sulthan Hospital Dg Radja Bulukumba Regency. This type of research is an analytic observational study with a "cross sectional" approach. Samples were 96 inpatients in Seruni. Sampling in this study was conducted with non-probability sampling techniques with consecutive sampling. Data collection is done through observation, questionnaires, and documentation. Data were analyzed with Chi-Square. The results of the Chi-Square analysis showed that there was a relationship between nurses' caring behavior and patient satisfaction (p = 0.001). The results of the analysis of the strength of the relationship indicate the direction of a positive correlation with the strength of a strong correlation.